Pengaruh Word Of Mouth Dan Kepercayaan Terhadap Keputusan Pengambilan Kredit Usaha Rakyat (KUR) Bank Bni Unit Jalan Baru Kabupaten Karawang - Ismi Salamah; Ajat Sudrajat (COSTING : Journal of Economic, Business and Accounting, 2021)
This study aims to determine the description of the variable word of mouth, customer trust, and decision making of people's business credit (KUR) at Bank BRI Unit Jalan Baru, Karawang Regency. In addition, this study aims to determine the effect partially and simultaneously between word of mouth and customer trust on the decision to make people's business credit (KUR) at Bank BRI Unit Jalan Baru, Karawang Regency. The type of data used in this research is quantitative data. This research was conducted on customers of the People's Business Credit (KUR) BRI Bank Unit Jalan Baru, Karawang Regency. The analysis model used in this research is the path analysis model. Based on the results of descriptive analysis, it shows that the word of mouth variable gets an average score of 474 on the agreeing criteria, then the customer trust variable gets an average score of 435.5 in the agreeing criteria, while the people's business credit decision-making variable (KUR) gets an average -The average score of 494.5 is on the agreed criteria. Based on the results of hypothesis testing, it shows that there is a partial and simultaneous influence on word of mouth and customer trust on the decision of making people's business credit (KUR) at Bank BRI Unit Jalan Kabupaten Karawang. Keyword : Word of mouth, Costumer Trust, Dicision Making Kredit